Ácido salicílico como elicitor abiótico no cultivo in vitro de plantas de Alternanthera tenella Colla - Brandão, Isabel Rodrigues (2012)
Alternanthera tenella Colla (Amaranthaceae), popularly known as "apaga-fogo", presents bioactive compounds as betacyanin and phenolics compounds being utilized in folk medicine as diuretic, anti-inflammatory and antipyretic. The use of elicitors allies with the tissue culture is an alternative to promote changes in secondary metabolism of plants, because it can stimulate the production of biologically active compounds, but may become harmful to plant growth. This present work aimed to evaluate the influence of salicylic acid on the growth of plants of A. tenella cultivated in vitro and verify their potential to optimize the production of phenolic compounds, flavonoids and betacyanin, and to verify the antioxidant capacity of the plant extracts. For this, in a first experiment, nodal segments were inoculated in MS medium with different concentrations of salicylic acid (0, 100, 200, 300 and 400 μM) where they remained for 35 days. The plants were evaluated for growth and betacyanin concentrations and of total phenolic compounds when exposed to different concentrations of elicitors. Separately, in a second experiment, the plants grown up on the vermiculite substrat plus of MS liquid medium and after 35 days were exposed to concentration 400 μM of salicylic acid for 0, 12, 36 and 48-h. After this period were quantified the bioactive compounds (betacyanin, total phenols and total flavonoids) and verified the antioxidant capacity in a non-enzyme from plants subjected to treatments. In relation to growth variables the elicitors was shown to be visibly harmful, occurring decreased of mean already on the lowest concentration used (100 μM). The concentration of 300 μM salicylic acid promoted an increase in the quantity of betacyanin, as for total phenolic compounds, reaching 366% and 180% respectively compared to control. The time of 36 hours of exposure of plants to salicylic acid resulted in the largest mean both betacyanin content of, as for total phenolic compounds. Now for total flavonoids, the highest exposure times (36 and 48-h) the elicitors had the lowest averages, differing from control and of 12-h of exposure. The extracts of leaf of apaga-fogo presented higher antioxidant capacity when subjected to 36 and 48-h of exposure to salicylic acid. Based on the results we can conclude that the use of elicitors in the culture medium is unfavorable to the growth of plants of A. tenella in vitro, however increases of form significantly the production of compounds of interest in this study, well as the antioxidant capacity of the plant extracts.